TRANSLATION OF TEXTS OF TOURISM SPHERE BASED ON COMPARISON OF CHINESE AND WESTERN CULTURES (Journal of Oriental Studies, 2018)
As tourism industry developed in China rapidly, there appeared a need to translate tourism texts from Chinese into English. Translator does not translate the text into simple mechanical interpretations, but includes complicated intercultural communication. Chinese and English have two different cultures, so the translator should focus on cultural differences between these two languages. Good tourist text will be of interest to potential readers and will help to develop the Chinese tourism industry, as well as enrich Chinese culture and target culture. The article analyzes cultural differences between the East and the West in terms of thinking, historical basis, religion and speech. It also explores some of the principles and methods of translation, such as the text of the tourism text, as well as overwriting, adding and deleting.